Evaluation of Environmental Policies in Mitigating the Impact of Climate Change on Biodiversity in Bali - Arpan, ‎ (KnE Social Sciences, 2025)
Global climate change has had a significant impact on biodiversity in the Province of Bali, which holds a strategic position as a center of tropical ecology and ecological culture. The island faces environmental pressures due to rising temperatures, sea level rise, and extreme weather changes that disrupt ecosystem balance, particularly in critical areas such as tropical forests, mangroves, and coral reefs. This study aims to evaluate the effectiveness of the Bali Provincial Government’s environmental policies in responding to the challenges of climate change on biodiversity. The approach used is legal-sociological with a descriptive-analytical method, through field studies, interviews with stakeholders, and analysis of legal documents and regional policies. The results of the study show that policies such as the Regional Action Plan for Climate Change Adaptation and Mitigation (RAD-API/MPI) and Bali Governor Regulation No. 97 of 2018 have demonstrated the local government’s commitment to climate mitigation and environmental protection. However, their implementation still faces institutional barriers, regulatory overlaps, and low local community participation. On the other hand, community-based strategies such as customary forest management, mangrove rehabilitation, and environmental education have made positive contributions to strengthening ecosystem resilience. An integrative, science-based policy approach and sustainable community capacity building are needed to ensure the effective protection of biodiversity in Bali in the face of climate change threats.